2023
DOI: 10.1007/s00264-022-05685-7
|View full text |Cite
|
Sign up to set email alerts
|

Corrective bandages and daily manipulations for treatment of congenital vertical talus: a thirteen year follow-up

Abstract: Purpose To analyze the results of a conservative method for treating congenital vertical talus in children with early start and to know in which cases surgical treatment was needed. Methods A retrospective analysis of all children diagnosed with idiopathic vertical talus was carried out during the years 2008–2021. Thirty-two children (46 feet) were finally included. Children were treated with serial manipulations, muscle stimulation, and corrective bandage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(47 reference statements)
0
0
0
Order By: Relevance
“…Additionally, the talo-first metatarsal angle (Meary’s angle) on the AP view is often greater than 30 degrees, further signifying hindfoot valgus. On the lateral view, critical radiographic parameters include the tibiocalcaneal angle, kite angle, and Meary’s angle (Figure 2A , 2B ) [ 17 ]. In cases of CVT, the long axis of the talus aligns vertically relative to the first metatarsal, and the calcaneus is affected by severe equinus, thereby increasing the lateral Meary’s, kite, and tibiocalcaneal angles [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the talo-first metatarsal angle (Meary’s angle) on the AP view is often greater than 30 degrees, further signifying hindfoot valgus. On the lateral view, critical radiographic parameters include the tibiocalcaneal angle, kite angle, and Meary’s angle (Figure 2A , 2B ) [ 17 ]. In cases of CVT, the long axis of the talus aligns vertically relative to the first metatarsal, and the calcaneus is affected by severe equinus, thereby increasing the lateral Meary’s, kite, and tibiocalcaneal angles [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
“…Historically, nonoperative treatment consisted of serial manipulation and casting [ 17 ]. Over the years, studies concluded that serial casting alone was not sufficient, and that combination with surgical treatment resulted in superior outcomes with reduced relapse [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation